Layanan Bimbingan Konseling SMP N 1 Parigi Untuk Mengurangi Kecanduan Game Online Pada Siswa - Nisa Nurrohmah; Riksa Iqomah; Bela Safitri; Deni Faslah; Annisa Kania Fauzani Tarigan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Online games are games that are liked by teenagers today and one of them is SMP N 1 Parigi students. To anticipate and minimize the bad impact that will occur for online students, it is necessary to have guidance from the school and especially from the parents of the students themselves. The purpose of this study was to determine the guidance and counseling services in overcoming the problems of students who are addicted to online games, special services to overcome online game addiction. This research is a qualitative research using a descriptive approach. Data were collected by interview, observation, documentation and recording. The results showed that the positive and negative impacts of online game addiction on students' academic behavior patterns and student learning outcomes. To reduce online game addiction in students, guidance and counseling services used by teachers are group guidance services. That is by providing an understanding of the dangers of playing excessive online games, both in groups which BK is often done in class or individually through group guidance services.